1996
DOI: 10.1046/j.1365-2710.1996.89675896.x
|View full text |Cite
|
Sign up to set email alerts
|

Near-patient stability studies

Abstract: Approaches to performing stability tests on formulations developed in hospitals, defined as the near-patient situation, are reviewed. Emphasis is placed on the selection and validation of storage conditions and the statistical methodology necessary to ensure confidence in the results obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The stabilities of vancomycin 50 mg/ml in all vehicles were examined by absorbance and calculated with standard vancomycin to percent of the labeled amount. It was found that more than 90% of the initial vancomycin concentration remained after 30 days at 2-8 o C, as shown in Fig 1a [10]. The MIC from broth dilution of vancomycin 50 mg/ml of all vehicles were in an acceptable range of 0.5-2.0 µg/ml after 30 days at 2-8 o C in accordance with CLSI 2011 guidelines [7].…”
Section: Resultssupporting
confidence: 73%
“…The stabilities of vancomycin 50 mg/ml in all vehicles were examined by absorbance and calculated with standard vancomycin to percent of the labeled amount. It was found that more than 90% of the initial vancomycin concentration remained after 30 days at 2-8 o C, as shown in Fig 1a [10]. The MIC from broth dilution of vancomycin 50 mg/ml of all vehicles were in an acceptable range of 0.5-2.0 µg/ml after 30 days at 2-8 o C in accordance with CLSI 2011 guidelines [7].…”
Section: Resultssupporting
confidence: 73%
“…A decrease of no more than 10% is typically accepted as a stability limit for extemporaneously formulated ophthalmic solutions and has been used by previous studies addressing the stability of voriconazole in solution. 9,15,16…”
Section: Discussionmentioning
confidence: 99%
“…9,16,17 Although there was a statistically significant drop in voriconazole concentration at the 40°C storage temperature between day 0 and day 30, no solution fell below 94% of the original concentration, which is well above the 90% limit for extemporaneously prepared ophthalmic solutions. 9,15,16 Although voriconazole appears to remain stable at the studied temperatures, efficacy of the solutions was not evaluated. In addition, all solutions were maintained at a constant temperature for 30 days, only being briefly removed from the incubators for sample collection.…”
Section: Discussionmentioning
confidence: 99%